2014
DOI: 10.1007/s00726-014-1751-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of l-glutamine supplementation on maternal and fetal hemodynamics in gestating ewes exposed to alcohol

Abstract: Not much is known about effects of gestational alcohol exposure on maternal and fetal cardiovascular adaptations. This study determined whether maternal binge alcohol exposure and L-glutamine supplementation could affect maternal-fetal hemodynamics and fetal regional brain blood flow during the brain growth spurt period. Pregnant sheep were randomly assigned to one of four groups: saline control, alcohol (1.75–2.5 g/kg body weight), glutamine (100 mg/kg body weight) or alcohol + glutamine. A chronic weekend bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
8
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 105 publications
2
8
1
Order By: Relevance
“…This result suggests a reduction in oxidative stress in response to glutamine supplementation. Similarly, numerous well-designed investigations have consistently indicated that glutamine increases anti-oxidative capacity in mice (Ren et al 2014b;Cruzat et al 2014), rats (Xu et al 2014), pigs (Wu et al 2011b(Wu et al , 2013cWang et al 2008), and sheep (Sawant et al 2014;Washburn et al 2013). Furthermore, we found that dietary supplementation with 0.5 % glutamine decreased the expression of virulence factors of P. multocida, as we previously reported (Ren et al 2013e).…”
Section: Discussionsupporting
confidence: 80%
“…This result suggests a reduction in oxidative stress in response to glutamine supplementation. Similarly, numerous well-designed investigations have consistently indicated that glutamine increases anti-oxidative capacity in mice (Ren et al 2014b;Cruzat et al 2014), rats (Xu et al 2014), pigs (Wu et al 2011b(Wu et al , 2013cWang et al 2008), and sheep (Sawant et al 2014;Washburn et al 2013). Furthermore, we found that dietary supplementation with 0.5 % glutamine decreased the expression of virulence factors of P. multocida, as we previously reported (Ren et al 2013e).…”
Section: Discussionsupporting
confidence: 80%
“…We can deduce using Poiseuille's equation that resistance is inversely proportional to the radius to the fourth power, and thus changes in diameter observed in our study can lead to large significant decreases in uterine blood flow. These data are consistent with previous reports demonstrating ~40% decrease in uterine blood flow (UBF) following chronic binge alcohol exposure in sheep (Sawant, Ramadoss, Hankins, Wu, & Washburn, 2014). Chronic alcohol-induced UBF decrease of about ~40% would lead to a reduction in the uterine artery radius to normalize the shear, as noted in our study.…”
Section: Discussionsupporting
confidence: 93%
“…Recently, it has been reported that administration of alcohol to pregnant ewes led to a 21-30 % reduction in the plasma concentrations of glutamine and related amino acids, Furthermore, acute administration of glutamine to ewes, together with alcohol administration, was able to improve the profile of most amino acids (including citrulline and arginine) in both maternal and fetal plasma (Washburn et al 2013). L-Glutamine supplementation is able to mitigate the alcohol-induced acid-base imbalances and the alterations of the fetal regional brain blood flow (Sawant et al 2014).…”
Section: Glutamate/glutamine and Reproductionmentioning
confidence: 99%